PENERAPAN PENDEKATAN ETNOMATEMATIKA BERORIENTASI MOTIF UKIRAN RUMAH GADANG TERHADAP KEMAMPUAN PEMAHAMAN KONSEP PESERTA DIDIK KELAS IX SMPN 4 PADANG - Choiria Elwardha (Departemen Matematika, 2021)
One of the goals of learning mathematics is so that students have a good understanding of concepts. However, in reality the understanding of students' concepts at SMPN 4 Padang is still low. One solution that can be used to overcome these problems is to use an ethnomathematical approach that is oriented towards carving motifs on the rumah gadang. The purpose of this study was to determine and describe the development of the ability to understand mathematical concepts of grade IX students of SMP N 4 Padang after using the Ethnomathematical Approach. Based on data analysis, concluded that the development of students' conceptual understanding using an ethnomathematical approach oriented to carving motifs in the rumah gadang in class IX of SMPN 4 Padang experienced an increase in several indicators of concept understanding, that is restating the concept, classifying objects based on whether or not the requirements were met, form concepts, identify the properties of operations or concepts, apply concepts logically, provide examples and non-examples of concepts, present concepts in various forms of mathematical representation, and connect various concepts in mathematics and outside mathematics. Keywords – Concept Understanding, Ethnomathematical Approach, Rumah Gadang